Epidemiological study of Tinea corporis in Al-Najaf City and the possible sources of infection - Ahmed Rashad Rasool; Amel Mustafa Kamil; Dhakam Mohammed Abbas (Romanian Journal of Infectious Diseases)
Background and objectives. Tinea corporis is a common superficial fungal skin infection presenting complaints in daily practice that can lead to serious consequences caused by dermatophytes. This disease has a significant influence on public health and social life since its spread can be difficult to manage and has a high rate of recurrence. This study aims to determine the demographic characteristics and the possible source of infection with Tinea corporis in Al-Najaf City, Iraq. Materials and methods. A cross-sectional study was conducted on 190 Tinea corporis patients from the 1st of April 2023 to the 31st of July 2023 in the three specialized hospitals in Al-Najaf city all these patients were subjected to a questionnaire developed by the researcher. The questionnaire includes 4 domains regarding sociodemographic characteristics, personal habits, housekeeping habits, and possible sources of infection of the participants. Results. This study found that Tinea corporis affected both males and females equally in the study sample. While the age 20-29 and 30-39-years-old were the most highly affected (20% for each), the lowest was age ≥60 years old (7.1%). The possible source was the human-related possible source (31.1%), animal-related possible source (12.1%), soil-related possible source (5.8%), and among human-related possible source the household-related possible source was of 86.4%. Conclusions. There was no domination of one gender upon the other regarding Tinea corporis infection. Tinea corporis affects post-puberty at the highest rates and the elderly at the lowest rates. The most possible source of infection was human-related and especially household-related.